FUNGSI BIMBINGAN KONSELING BAGI PESERTA DIDIK DI SEKOLAH - Abdi Husein Nasution (CV Edu Tech Jaya, 2023)
This research aims to find out how important guidance and counseling are. BK is intended for all counselees. This means that guidance is given to all counselors or counselors, both those without problems and those with problems; both men and women; both children, teenagers and adults. In this case the approach used in guidance is more preventive and developmental rather than healing (curative); and group techniques are preferred over individual techniques. Guidance and counseling as an individuation process. Each counselee is unique (different from one another), and through guidance counselees are helped to maximize the development of their uniqueness. This principle also means that the focus of assistance is the counselee, even though the guidance service uses group techniques.